The Financial Crisis and the Changing Dynamics of the Yield Curve - Morten L. Bech; Yvan Lengwiler (University of Basel, Center of Business and Economics (WWZ), 2012)
We present evidence on the changing dynamics of the yield curve from 1998 to 2011. We identify four different phases. As expected, the financial crisis represents a period of elevated yield volatility, but it can be split into two distinct periods. The split occurs when the Federal Reserve reached the zero lower bound. This bound suppressed volatility in the short end of the yield curve while increasing volatility in the long end — despite lower overall volatility in financial markets. In line with previous studies, we find that announcements with regard to the Federal Reserve's large scale asset purchases reduce longer term yields. We also quantify the effect of widely observed economic news, such as the non-farm payrolls and other items, on the yield curve.
Keywords: E43; E52; 330; term structure of interest rates; financial crisis; interest rate dynamics; LSAP; unconventional monetary policy; Öffentliche Anleihe; Zinsstruktur; Finanzkrise; Geldpolitik; USA